THE POTENTIAL OF Clathria reinwardtii as BIOACCUMULATOR OF HEAVY METAL Cu - Lydia Melawaty; Alfian Noor; Tjodi Harlim; Nicole de Voogd (Hasanuddin University, 2014)
Heavy metal Cu is an essential metal required by living organisms but a pollutant in water environment when existed in a level above the treshold level. The capability of sponge Clathria reinwardtii in accumulating heavy metals was analyzed according to modified Müller et al. (1998) method, and the sediment was analyzed according to Loring and Rantala in Rochyatun et al., (2006). Cu concentrations were measured by ICP-OES. The results indicate that Clathria reinwardtii was capable of accumulating the highest Cu level compared to other sponges. The highest Cu level analyzed in Clathria reinwardtii was 161.3 mg/kg.